2014
DOI: 10.1016/j.atherosclerosis.2014.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid and the risk of mortality during 23 years follow-up in the Scottish Heart Health Extended Cohort Study

Abstract: Background Elevated uric acid is a prevalent condition with controversial health consequences. Observational studies disagree with regard to the relationship of uric acid with mortality, and with factors modifying this relationship. Objective We examined the association of serum uric acid with mortality in 15,083 participants in the Scottish Heart Health Extended Cohort (SHHEC) Study. Methods Serum uric acid measured at study enrollment. Death was ascertained using both the Scottish death register and reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
49
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 71 publications
4
49
1
1
Order By: Relevance
“…Barbieri et al [22] further showed that higher uric acid levels are significantly associated with higher prevalence of severe coronary artery disease only in women. Their findings are similar to ours, and this sex-linked difference was also found in other larger studies, such as the Chicago Heart Association Detection Project [23], National Health and Nutrition Examination Survey I epidemiologic follow-up study [24], post hoc analysis of the Losartan Intervention For Endpoint reduction in hypertension trials [25], and Scottish Heart Health Extended Cohort study [26]. The Scottish Heart Health Extended Cohort study demonstrated that uric acid level is more strongly associated with mortality in women than in men [26].…”
Section: Discussionsupporting
confidence: 90%
“…Barbieri et al [22] further showed that higher uric acid levels are significantly associated with higher prevalence of severe coronary artery disease only in women. Their findings are similar to ours, and this sex-linked difference was also found in other larger studies, such as the Chicago Heart Association Detection Project [23], National Health and Nutrition Examination Survey I epidemiologic follow-up study [24], post hoc analysis of the Losartan Intervention For Endpoint reduction in hypertension trials [25], and Scottish Heart Health Extended Cohort study [26]. The Scottish Heart Health Extended Cohort study demonstrated that uric acid level is more strongly associated with mortality in women than in men [26].…”
Section: Discussionsupporting
confidence: 90%
“…Higher levels of serum uric acid (SUA) are confirmed in men than in women at all ages [1]. Many studies [2][3][4][5] indicated excess mortality in women than men, but others [6,7] did not confirm these findings. Most studies on SUA levels and mortality risk were conducted in a single sex populations [8][9][10][11] or not conducted gender specific analyses [12].…”
mentioning
confidence: 94%
“…Overall quality of the included studies was good (range from 6 to 8) based on a 9-star NOS scales. Six studies [2][3][4][5][6][7] reported data on all-cause mortality according to the gender. Compared the highest to lowest SUA category, pooled RR of all-cause mortality was 1.15 (95% CI 0.89-1.49) for women and 1.13 for men (Fig.2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated uric acid levels often accompany high blood pressure (1,2) and are associated with cardiovascular disease risk (37). Recently, several trials of urate-lowering therapy have shown that short-term reductions in uric acid are associated with a reduction in blood pressure (811).…”
mentioning
confidence: 99%